2020
DOI: 10.1016/j.chiabu.2020.104667
|View full text |Cite
|
Sign up to set email alerts
|

Is the psychological impact of exposure to COVID-19 stronger in adolescents with pre-pandemic maltreatment experiences? A survey of rural Chinese adolescents

Abstract: Highlights A larger number of ACEs predict substantial higher levels of PTSS and anxiety. Experienced exposure and fear of exposure also predict more PTSS and anxiety. Childhood abuse and neglect may exacerbate the impact of exposure on mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 59 publications
3
87
0
Order By: Relevance
“…Of the 16 studies reviewed, 7 were conducted in China, 2 in the United States, 2 in Canada, and 1 each in Denmark, Germany, Japan, the Philippines, and the United Kingdom. All of the 16 studies utilized a quantitative methodology [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Among the studies, 12 (75%) were conducted online and 4 (25%) did not clearly report the study format.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 16 studies reviewed, 7 were conducted in China, 2 in the United States, 2 in Canada, and 1 each in Denmark, Germany, Japan, the Philippines, and the United Kingdom. All of the 16 studies utilized a quantitative methodology [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Among the studies, 12 (75%) were conducted online and 4 (25%) did not clearly report the study format.…”
Section: Resultsmentioning
confidence: 99%
“…One study in China conducted by Duan et al [ 17 ] identified an association between depression and COVID-19 related addiction in using social media, such as smartphone addiction ( OR = 1.844, 95% CI : 1.29 to 2.811), and internet addiction ( OR = 3.107, 95% CI : 1.252 to 7.708). Guo et al [ 23 ] identified an association between COVID-19 related stress and depression ( β = 0.33, t = 11.49, p < 0.001). However, the study conducted by Chen et al in China [ 19 ] failed to establish a significant correlation between depression and COVID-19 related factors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further studies could better investigate the autonomy issue related to COVID-19 emergency considering the role family and different parenting models can play. For instance, very few studies have investigated the role of pre-pandemic maltreatment experience (Guo et al, 2020) or other experience related to family environment. Our results suggest the duplex role of family and invite scholars and professionals to design specific intervention programs for adolescents with family vulnerability.…”
Section: Limitations and Conclusionmentioning
confidence: 99%